Freshwater cyclopoids and harpacticoids (Crustacea: Copepoda) from the Gnangara Mound region of Western Australia - Tang, Danny; Knott, Brenton (Zootaxa, 2009)
The Gnangara Mound is a 2,200 km 2 unconfined aquifer located in the Swan Coastal Plain of Western Australia. This aquifer is one of the most important ground water resources for the Perth Region and supports a number of groundwaterdependent ecosystems, such as the springs of Ellen Brook and root mat communities of the Yanchep Caves. Although freshwater copepods have been documented previously from those caves and springs, their specific identity were hitherto unknown. The current work formally identifies copepod samples collected from 23 sites (12 cave, three bore, five spring and three surface water localities) within the Gnangara Mound region. Fifteen species were documented in this study: the cyclopoids Australoeucyclops sp., Eucyclops edytae sp. nov., Macrocyclops albidus (Jurine, 1820), Mesocyclops brooksi Pesce, De Laurentiis & Humphreys, 1996, Metacyclops arnaudi (G. O. Sars, 1908), Mixocyclops mortoni sp. nov., Paracyclops chiltoni (Thomson, 1882), Paracyclops intermedius sp. nov. and Tropocyclops confinis (Kiefer, 1930), and the harpacticoids Attheyella (Chappuisiella) hirsuta Chappuis, 1951, Australocamptus hamondi Karanovic, 2004, Elaphoidella bidens (Schmeil, 1894), Kinnecaris eberhardi (Karanovic, 2005), Nitocra lacustris pacifica Yeatman, 1983 and Paranitocrella bastiani gen. et sp. nov. Tropocyclops confinis is recorded from Australia for the first time and A. (Ch.) hirsuta and E. bidens are newly recorded for Western Australia. The only copepod taxa endemic to the Gnangara Mound region are E. edytae sp. nov. (occurs primarily in springs and rarely in the Yanchep National Park Caves) and P. bastiani gen. et sp. nov. (confined to the Yanchep National Park Caves containing tuart root mats). Paracyclops chiltoni was the most common species, whilst T. confinis and N. l. pacifica were rarely encountered. Metacyclops arnaudi was the only taxon absent from ground waters. The copepod fauna recorded in the caves and springs of the Gnangara Mound region are comparable, with respect to species richness, endemicity and the varying degrees of dependency on ground water, to those reported from similar habitats in South Australia and Western Australia. Restoring the root mats and maintaining permanent water flow within the Yanchep Caves, as well as minimising urban development near the Ellen Brook Springs, are essential to protect the copepod species, particularly the endemic P. bastiani gen. et sp. nov. and E. edytae sp. nov., inhabiting these unique ground water environments.